CONSTRUCTION OF ASSYMETRIC QUANTUM CODES FOR NESTED CODE PAIRS - BHAKTI WIRA TAMA (NIM: 20117019), YANUAR
A quantum code can be constructed from linear codes. With stabilizer method, if we have a linear code that is an Fq-subspace of F2nq, we can have a quantum code with length (n)which is a C-subspace of C(qn)where (q) is a prime power. The difference between symmetric quantum code and asymmetric quantum code lies in probability of dz(phase error) and dx(bit error). We can construct an asymmetric quantum code by evaluating multivariate polynomials at the points of Cartesian products of subsets of a finite field. In this thesis we will consider nested pair codes, and we can use Feng-Rao bound and CSS quantum code construction to construct nested quantum codes. After that, the construction by evaluating polynomials will be compared with another construction of quantum codes such as Reed-Solomon codes, or codes constructed by Gilbert-Varshamov bound.